Seminal Plasma Exposures Strengthen Vaccine Responses in the Female Reproductive Tract Mucosae - Marlin, Romain; Nugeyre, Marie-Thérèse; Tchitchek, Nicolas; Parenti, Matteo; Lefebvre, Cécile; Hocini, Hakim; Benjelloun, Fahd; Cannou, Claude; Nozza, Silvia; Dereuddre-Bosquet, Nathalie; Levy, Yves; Barré-Sinoussi, Françoise; et al. (Frontiers in Immunology, 2019)
HIV-1 sexual transmission occurs mainly via mucosal semen exposures. In the female reproductive tract (FRT), seminal plasma (SP) induces physiological modifications, including inflammation. An effective HIV-1 vaccine should elicit mucosal immunity, however, modifications of vaccine responses by the local environment remain to be characterized. Using a modified vaccinia virus Ankara (MVA) as a vaccine model, we characterized the impact of HIV-1+ SP intravaginal exposure on the local immune responses of non-human primates. Multiple HIV-1+ SP exposures did not impact the anti-MVA antibody responses. However, SP exposures revealed an anti-MVA responses mediated by CD4+ T cells, which was not observed in the control group. Furthermore, the frequency and the quality of specific anti-MVA CD8+ T cell responses increased in the FRT exposed to SP. Multi-parameter approaches clearly identified the cervix as the most impacted compartment in the FRT. SP exposures induced a local cell recruitment of antigen presenting cells, especially CD11c+ cells, and CD8+ T cell recruitment in the FRT draining lymph nodes. CD11c+ cell recruitment was associated with upregulation of inflammation-related gene expression after SP exposures in the cervix. We thus highlight the fact that physiological conditions, such as SP exposures, should be taken into consideration to test and to improve vaccine efficacy against HIV-1 and other sexually transmitted infections.